Association between maternal ritodrine hydrochloride administration during pregnancy and childhood wheezing up to three years of age: The Japan environment and children's study. Issue 7 (29th June 2021) - Murata, Tsuyoshi; Kyozuka, Hyo; Yasuda, Shun; Fukuda, Toma; Yamaguchi, Akiko; Maeda, Hajime; Sato, Akiko; Ogata, Yuka; Shinoki, Kosei; Hosoya, Mitsuaki; Yasumura, Seiji; Hashimoto, Koichi; et al.
Abstract: Background: The effects of maternal ritodrine hydrochloride administration (MRA) during pregnancy on fetuses and offspring are not entirely clear. The present study aimed to evaluate the association between MRA and childhood wheezing using data from a nationwide Japanese birth cohort study. Methods: This study analyzed the data of the participants enrolled in the Japan Environment and Children's Study, a nationwide prospective birth cohort study, between 2011 and 2014. Data of women with singleton live births after 22 weeks of gestation were analyzed. The participants were divided according to MRA status. Considering childhood factors affecting the incidence of wheezing, including smoking environment and childhood viral infections, a logistic regression model was used to calculate odds ratios for "wheezing ever, " diagnosis of asthma in the last 12 months, and "asthma ever" in women with MRA, with women who did not receive MRA as the reference. Additionally, participants were stratified by term births, and odds ratios for outcomes were calculated using a logistic regression model. Results: A total of 68, 123 participants were analyzed. The adjusted odds ratio for wheezing was 1.17 (95% confidence interval, 1.12–1.22). The adjusted odds ratios for the other outcomes did not significantly increase after adjusting for childhood factors. The same tendency was confirmed after excluding women with preterm births. Conclusion: MRA was associated with a slightly increased incidence of childhood wheezing up to three years, irrespective of term or preterm birth status. It is important that perinatal physicians consider the potential effects of MRA on the offspring's childhood health.